Psychological Strengthening and Assistance through Goal Setting Strategy to Increase Badminton Athletes' Fighting Power in Competitions - Kusuma, Angga Indra; Pratama, Raditya; Puriana, Ramadhany Hananto; Wahyono, Muhammad; Harmono, Bayu Akbar; Putra, Ismawandi Bripandika (⁠International Journal of Asia Pacific Community Service, 2025)
This community service aims to increase the motivation and fighting spirit of badminton athletes through the implementation of goal setting strategies and intensive psychological assistance. The main focus is to equip young athletes with the ability to manage mental stress and set clear training goals so that they consistently train and are ready to face competitions with confidence. In addition, this service also contributes to athlete development at the community level by building a training ecosystem that supports comprehensive mental and emotional development, as well as increasing the capacity of coaches in implementing effective psychological approaches. The methods used include goal setting technique workshop training, group counseling sessions to share experiences, and routine assistance for three months. The implementation is carried out at local badminton clubs, involving athletes, coaches, and club administrators. Each stage begins with measuring the motivation and mental readiness of athletes using psychological instruments, followed by providing interactive materials and practices, and ending with an evaluation to ensure positive changes. It is hoped that the results of this service will create badminton athletes who are technically superior and mentally tough, able to compete better, and have a long-term positive impact on regional sports development. This service supports the development of human resources for badminton sports in a sustainable and comprehensive manner.